Islamic finance and economic growth: the Malaysian experience - Kassim, Salina (Elsevier, 2016)
The increasing presence of Islamic banking and finance in Malaysia's financial sector and the country's exemplary role in the global Islamic finance industry has called for an evaluation of the contribution of Islamic finance to the real economic activity. This study applies the ARDL approach on quarterly data set covering the period from 1998 to 2013 to empirically investigate the impact of Islamic finance on performances of major macroeconomic indicators. The results suggest that the Islamic finance has started to make important contributions to the real economy by effectively carrying-out the financial intermediation role of pooling and channelling funds to the investment activities. In view of the important contributions of Islamic finance to the Malaysian economy, continuous efforts need to be undertaken to expand the industry. This includes refinement of the legal and regulatory framework to enable healthier growth of the industry, thus further strengthens Malaysia's position as the leader in promoting Islamic finance at the global level.